2016
DOI: 10.1093/ageing/afw024.03
|View full text |Cite
|
Sign up to set email alerts
|

3 Impact of an Integrated Medicines Management (Imm) Service on Preventable Medicines Related Readmission (Pmrr) to Hospital

Abstract: Topic: Medication contributes to 5-20% of hospital admissions of which half are preventable (Pirmohamed M et al BMJ. 2004;329:15-19). Avoidable medicines related harm in England was estimated for 2014 as £1-£2.5bn. In 2010 the Department of Health issued guidance that NHS Trusts would no longer be fully reimbursed for emergency readmissions within 30 days of discharge, making reducing preventable medicines related readmission (PMRR) a priority.The National Service Framework for Older People (2001 London: Depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Patients identified as high‐risk receive enhanced clinical pharmacy input during their hospital stay and post‐discharge support if required. A case–control study of 836 patients found that there was a statistically significant reduction in medicines‐related readmissions in patients receiving this service ( P < 0.002) . A similar integrated medicines management model in Sweden has also demonstrated a statistically significant reduction in medication‐related hospital admissions and associated cost savings …”
Section: Discussionmentioning
confidence: 95%
“…Patients identified as high‐risk receive enhanced clinical pharmacy input during their hospital stay and post‐discharge support if required. A case–control study of 836 patients found that there was a statistically significant reduction in medicines‐related readmissions in patients receiving this service ( P < 0.002) . A similar integrated medicines management model in Sweden has also demonstrated a statistically significant reduction in medication‐related hospital admissions and associated cost savings …”
Section: Discussionmentioning
confidence: 95%